Rekonstruksi Sistem Demokrasi Lokal di Indonesia - Hady, Nuruddin (Universitas Negeri Malang, 2022)
This study aimed to analyze local democracy in the old order, new order, and reform eras and reconstruct local democracy in Indonesia. The study was sociological juridical with a statutory approach, a historical approach, and a conceptual approach. Local democracy was reflected in the election of regional heads from the old order era until the reformation, which changed under the applicable laws and regulations. The Regional People's Representative Council elected regional heads in the old order era. In contrast, in the new order era, they were elected by the Regional People's Representative Council based on mutual agreement with the Minister of Home Affairs or the Governor. The filling of regional head positions in the reform era, which the Regional People's Representative Council previously carried out, was done directly by the people. Indonesia reconstructed local democracy through several alternatives: regional heads elected by the Regional People's Representative Council, elected through determination, directly elected by the people, and elections in accordance with regional peculiarities.